Photoluminescence and scintillation properties of rare earth doped Lu2O3 single crystal grown by floating zone method - Takayuki Yanagida; Daisuke Nakauchi; Kai Okazaki; Takumi Kato; Kenichi Watanabe; Go Okada; Noriaki Kawaguchi (Optical Materials: X)
A series of Lu2O3 single crystals doped with rare earth (RE) ions (RE = Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb, dopant concentrations are 1 %) was synthesized by the floating zone method. Their photoluminescence (PL) and scintillation properties were evaluated. In PL, emissions due to 4f-4f transitions of trivalent rare earth ions were observed, and those doped with Nd3+, Eu3+, Tb3+ and Er3+ showed the highest emission intensities among the samples. As a scintillation property, those doped with Eu, Gd, and Dy showed a clear photoabsorption peak under 137Cs 662 keV γ-ray irradiation. Among them, the Eu3+-doped Lu2O3 showed the highest scintillation light yield of 67000 photons/MeV. The current work conducted the first systematic study of rare earth doped Lu2O3 single crystals grown by the floating zone method.